Analysis of the Application of Depreciation Methods, Useful Life, and Revaluation of Fixed Assets on Financial Performance at PT Perkebunan Nusantara IV Regional I - Hilmi, Hafizh; Syarvina, Wahyu; Nasution, Yenni Samri Juliati (Journal of Economics and Management Scienties, 2025)
This research aims to analyze the impact of depreciation methods, estimated useful life, and revaluation of fixed assets on the company's financial performance, with a case study on PT Perkebunan Nusantara IV Regional I. This study employs a descriptive quantitative approach by analyzing the company's financial statements and conducting interviews with relevant parties. The research results indicate that the depreciation method has a significant impact on financial performance, particularly in the Return on Asset (ROA), Return on Fixed Asset (ROFA), and Fixed Asset Turnover (FATO) ratios. The Declining Balance and Sum-of-the-Years' Digits methods yield higher performance ratios compared to the Straight-Line Method, especially in the initial period of asset use. Accurate estimation of useful life helps ensure the relevance of financial statements, supports the accuracy of asset provisioning, and maintains the stability of the company's equity. On the other hand, revaluation of fixed assets increases the value of assets and equity, but it also raises depreciation expenses, which can pressure net profit if not balanced with operational efficiency. This research provides recommendations for companies to choose a depreciation method that aligns with strategic needs, pay attention to accurate useful life estimates, and consider asset revaluation policies to enhance the relevance and accuracy of financial statements.